A colaboração entre intérprete e compositores através da encomenda e estreia das obras para percussão múltipla Estudo 1, de Carlos Santos e Átimo, de Rubens Fonseca. - Rafael de Mello Matos (2015)
This paper proposes the application of the theory of Michael Farrell Collaborative Circles in the analysis of collaborative processes between composers and performers. To illustrate this application, this paper presents an analysis of the relationship between percussionist Rafael Matos and composers Carlos dos Santos and Rubens Fonseca, through the process of commissioning, preparing and premiering the respective works Estudo n. 1 and Átimo for solo multiple percussion. Using this theory, I intend to create an alternative not only to document the interactions within the collaborative circles during the process of creating a musical work, but also to demonstrate that collaborative processes become essential elements in creative activity. As a result of this research, I present considerations regarding the importance of the dual role of an interpreter to document and build a performance based on proximity and exchange of experiences with composers.